Study on the mycobiota and mycotoxins of commercial equine feeds in Rio de Janeiro, Brazil - Keller, Kelly Moura (2008)
Colonization of feedstuffs and agricultural commodities by mycotoxins producer moulds is a significant problem worldwide. Contamination of feed ingredients, increases the risk of contamination of the finished products such as manufactured commercial feeds. Studies evaluating the risk of mycotoxins in the equine environment are scarce. The aims of this study were to evaluate the mycobiota present in commercial equine feeds and to determine total aflatoxins(AFs) and fumonisins (FBs). Thirty samples of 21 commercial equine feeds were collected at random from 5 different equestrian centers located in Rio de Janeiro, Brazil. Total fungal counts (CFU g-1) of equine feeds ranged from not detectable (ND) to 1.3 x 106 CFU/g onto DRBC medium. Penicillium spp. (52%) was the prevalent genera, followed by Aspergillus spp. (32.5%). Aspergillus niger aggregate (60%) and Aspergillus flavus (22%) showed the highest relative densities. Thirteen Penicillium spp. were isolated. All samples (100%) were contaminated with AFs at levels that varied between 1 and 44 μg/Kg. The 65% of these samples were positive to FBs contamination at levels ranging from 0.2 to 8.5 μg/g. Monitoring mycological and mycotoxicological quality of feed ingredients and commercial feedstuffs used in equine husbandry are critical for improving animal production and performance.